Differences In Mesenkimal Stem Cell Proliferation Between Bone Marrow Type Stem Cells And Wharton's Jelly Type Stem Cells - Mahendika, Devin; Arif, Muhammad; Julita, Ema; Ali, Hirowati (Jurnal EduHealth, 2024)
Various sources of stem cells in the human body, one of which is mesenchymal stem cells derived from bone marrow and Wharton's jelly. This study aims to determine differences in the proliferation count results of 2 stem cells from different sources, bone marrow and Wharton's jelly. The research was conducted using a true experimental design with in-vitro studies. Bone marrow and Wharton's jelly MSC were counted for their proliferation results at 24 hours, 48 hours, and 72 hours. The data then compared using the T-test method. The results of the study showed differences the results of the proliferation count between bone marrow and Wharton's jelly. Qualitatively, Wharton's jelly was seen in 24 hours, 48 hours, or 72 hours. However, quantitatively with statistical tests, the results that were not significant in the first 24 hours (p=0.053). At 48 hours, statistically significant results (p=0.007) were obtained because the cells began to proliferate rapidly and gave a clear difference, and at 72 hours, insignificant statistical results (p 0.074) were found because the cells were confluent and filled the substrate.The ability to reproduce is one of the characteristics possessed by stem cells. This process can be influenced by many factors so that between a culture can vary the speed of proliferation. Proliferation count showed that Wharton's jelly was more than bone marrow in 24 hours, 48 hours, or 72 hours. Different sources of MSC yield different proliferation results.